2016
DOI: 10.1017/s1751731116000185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stage of pregnancy on variance components, daily milk yields and 305-day milk yield in Holstein cows, as estimated by using a test-day model

Abstract: Pregnancy and calving are elements indispensable for dairy production, but the daily milk yield of cows decline as pregnancy progresses, especially during the late stages. Therefore, the effect of stage of pregnancy on daily milk yield must be clarified to accurately estimate the breeding values and lifetime productivity of cows. To improve the genetic evaluation model for daily milk yield and determine the effect of the timing of pregnancy on productivity, we used a test-day model to assess the effects of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The length of DO and calving interval changed with changing CR because CR affected the required number of AI services per conception. The total milk yield of a lactation was affected by CR because the shape of the lactation curve was affected by DO (Brotherstone et al, 2004;Olori et al, 1997;Yamazaki et al, 2016). DO evidently affected the calving interval and milking length.…”
Section: Equation Number Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…The length of DO and calving interval changed with changing CR because CR affected the required number of AI services per conception. The total milk yield of a lactation was affected by CR because the shape of the lactation curve was affected by DO (Brotherstone et al, 2004;Olori et al, 1997;Yamazaki et al, 2016). DO evidently affected the calving interval and milking length.…”
Section: Equation Number Equationmentioning
confidence: 99%
“…Therefore, the total milk yield of a lactation period and the annual milk yield may decrease. The milk yield in the late lactation period would decrease if DO is shortened (Brotherstone, Thompson, & White, ; Olori, Brotherstone, Hill, & McGuirk, ; Yamazaki et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, setting a sufficient voluntary waiting period regardless of milk yield will improve the uterine condition in early lactation, and careful management in the subsequent peak lactation period can provide a stable conception rate throughout the lactation period. Moreover, cows that conceived 90 d after calving have shown increased 305d milk yield compared with cows that conceived before 90 d (Yamazaki et al, 2016). Therefore, the extension of the voluntary waiting period to 90 d may lead to the maintenance of milk yield in addition to an increased conception rate.…”
Section: Discussionmentioning
confidence: 99%
“…The Holstein—Japan's main dairy cow—excels as a dairy breed, producing 8016 to 9531 kg of average milk yield over 305 days during the first to third lactation periods (Yamazaki et al, 2016). However, many studies have shown that Holstein cows are very sensitive to heat stress and suffer negative effects of heat stress on their milk yield and reproduction (e.g., Atagi et al, 2019; Bernabucci et al, 2014; Boonkum et al, 2011; Fuquay, 1981; Hagiya et al, 2020; Negri et al, 2021; Ravagnolo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%